25‐Hydroxycholesterol protects against acute lung injury via targeting MD‐2. Issue 11 (9th August 2018) - Ouyang, Wei; Zhou, Hui; Liu, Chao; Wang, Shiwei; Han, Yu; Xia, Jingyan; Xu, Feng
Abstract: Acute lung injury (ALI) is mainly caused by uncontrolled inflammatory response, and it remains without effective therapeutic options. 25‐hydroxycholesterol (25HC) has been reported to be a potent regulator of inflammation. The aim of this study was to investigate the effects of 25HC on lipopolysaccharide (LPS)‐induced ALI. C57BL/6 mice were pretreated with 25HC intraperitoneally before intratracheal exposure to LPS. Our results showed that 25HC pretreatment improved survival rate, attenuated the pathological changes of the lung and decreased the release of inflammatory cytokines in mice. Consistently, 25HC reduced expression of Toll‐like receptor (TLR4)‐mediated inflammatory cytokines in vitro. These effects of 25HC were obtained by preventing LPS binding to TLR4 via interaction with myeloid differentiation protein 2 (MD‐2). Crystal structure analysis suggested that 25HC could bind MD‐2 with high affinity into its hydrophobic pocket. Furthermore, LPS‐induced activation of Akt/NF‐κB pathway was partially down‐regulated by 25HC pretreatment. In summary, this study demonstrates that 25HC could inhibit the overwhelming inflammatory response through MD‐2 interaction, which suppresses Akt/NF‐κB signalling pathway. These findings suggest 25HC may be a promising candidate for ALI prevention.